Probiotic Escherichia coli Nissle 1917-derived outer membrane vesicles enhance immunomodulation and antimicrobial activity in RAW264.7 macrophages - Rujiu Hu; Hua Lin; Jing Li; Yuezhen Zhao; Mimi Wang; Xiaoqin Sun; Yuna Min; Yupeng Gao; Mingming Yang (BMC Microbiology, 2020)
Abstract Background Probiotic Escherichia coli Nissle 1917 (EcN) has been widely studied for the treatment of intestinal inflammatory diseases and infectious diarrhea, but the mechanisms by which they communicate with the host are not well-known. Outer membrane vesicles (OMVs) are produced by Gram-negative bacteria and deliver microbial molecules to distant target cells in the host, which play a very important role in mediating bacteria-host communication. Here, we aimed to investigate whether EcN-derived OMVs (EcN_OMVs) could mediate immune regulation in macrophages. Results In this study, after the characterization of EcN_OMVs using electron microscopy, nanoparticle tracking and proteomic analyses, we demonstrated by confocal fluorescence microscopy that EcN_OMVs could be internalized by RAW 264.7 macrophages. Stimulation with EcN_OMVs at appropriate concentrations promoted proliferation, immune-related enzymatic activities and phagocytic functions of RAW264.7 cells. Moreover, EcN_OMVs induced more anti-inflammatory responses (IL-10) than pro-inflammatory responses (IL-6 and TNF-α) in vitro, and also modulated the production of Th1-polarizing cytokine (IL-12) and Th2-polarizing cytokine (IL-4). Treatments with EcN_OMVs effectively improved the antibacterial activity of RAW 264.7 macrophages. Conclusions These findings indicated that EcN_OMVs could modulate the functions of the host immune cells, which will enrich the existing body of knowledge of EVs as an important mechanism for the communication of probiotics with their hosts.